If 5x - 17 ≥ 0, then |5x - 17| = 5x - 17 and the equation reduces to
-8 - 2 (5x - 17) = -14
-8 - 10x + 34 = -14
-10x = -40
x = 4
If 5x - 17 < 0, then |5x - 17| = -(5x - 17) = -5x + 17 and we have
-8 - 2 (-5x + 17) = -14
-8 + 10x - 34 = -14
10x = 28
x = 2.8
answer: positive
for example: -2 x -2 x -2 x-2
=4 x -2 x -2
=-8 x -2
=positive 16
Answer: y = 7.5
Step-by-step explanation:
Suppose that y varies directly with x
That is, y∝x
Convert y∝x to a full equation by introducing a constant k to the right hand side.
Therefore, y = kx
Given that y = 10 and x = 20
Substitute y and x in the equation above. We have;
10 = k(20)
10 = 20k
20k = 10
k = 10/20
k = 0.5
Since k = 0.5, the equation y = kx becomes y = 0.5x
Now, to find y if x = 15, substitute x in equation y = 0.5x
Therefore, y = 0.5(15)
y = 7.5
Answer:
Step-by-step explanation:
sin36=h/75
h=75sin36
h=44.08ft